The Role Of Virtual Communities Marketing In Building The Competitive Advantage Of Small And Medium Enterprises A field study on a sample of Syrian small and medium enterprises (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The research aimed to study the role of virtual communities marketing in building the competitive advantage of Syrian small and medium enterprises, by studying the role of the dimensions of virtual communities marketing, represented by: Interactivity, content, and credibility in building the competitive advantage of Syrian small and medium enterprises. The researcher relied on the descriptive analytical approach as a general research approach, where a questionnaire was designed and distributed to a deliberate sample of Syrian small and medium enterprises that have a presence in virtual communities. The number of questionnaires valid for statistical analysis was 75 questionnaires. The research concluded that there is a positive moral impact of virtual communities marketing in building the competitive advantage of Syrian small and medium enterprises. The dimensions of virtual communities marketing were ranked in terms of the strength of influence in building the competitive advantage of Syrian small and medium enterprises, according to the following order: content, Interactivity, and credibility.